Structural variation of mitochondrial genomes sheds light on evolutionary history of soybeans. (13th October 2021) - Liu, Hao; Yu, Junping; Yu, Xiaoxia; Zhang, Dan; Chang, Han; Li, Wei; Song, Haifeng; Cui, Zheng; Wang, Peng; Luo, Yixin; Wang, Fei; Wang, Dagang; et al.
SUMMARY: The architecture and genetic diversity of mitogenome (mtDNA) are largely unknown in cultivated soybean ( Glycine max ), which is domesticated from the wild progenitor, Glycine soja, 5000 years ago. Here, we de novo assembled the mitogenome of the cultivar 'Williams 82' (Wm82_mtDNA) with Illumina PE300 deep sequencing data, and verified it with polymerase chain reaction (PCR) and Southern blot analyses. Wm82_mtDNA maps as two autonomous circular chromosomes (370 871‐bp Chr‐m1 and 62 661‐bp Chr‐m2). Its structure is extensively divergent from that of the mono‐chromosomal mitogenome reported in the landrace 'Aiganhuang' (AGH_mtDNA). Synteny analysis showed that the structural variations (SVs) between two genomes are mainly attributed to ectopic and illegitimate recombination. Moreover, Wm82_mtDNA and AGH_mtDNA each possess six and four specific regions, which are absent in their counterparts and likely result from differential sequence‐loss events. Mitogenome SV was further studied in 39 wild and 182 cultivated soybean accessions distributed world‐widely with PCR/Southern analyses or a comparable in silico analysis. The results classified both wild and cultivated soybeans into five cytoplasmic groups, named as GSa–GSe and G1–G5; 'Williams 82' and 'Aiganhuang' belong to G1 and G5, respectively. Notably, except for members in GSe and G5, all accessions carry a bi‐chromosomal mitogenome with a common Chr‐m2. Phylogenetic analyses based on mtDNA structures and chloroplast gene sequences both inferred that G1–G3, representing >90% of cultigens, likely inherited cytoplasm from the ancestor of domestic soybean, while G4 and G5 likely inherited cytoplasm from wild soybeans carrying GSa‐ and GSe‐like cytoplasm through interspecific hybridization, offering new insights into soybean cultivation history. Significance Statement: We assembled the mitochondrial genome of the cultivated soybean 'Williams 82', providing a valuable reference for soybean mitogenome research and cultivar improvement. We showed that wild and cultivated soybeans predominantly possess a novel bi‐chromosomal mitogenome, and illustrated that cytoplasmic genomes in modern cultivated soybean originated from at least three wild progenitors with different types of cytoplasm through domestication and interspecific hybridization events, shedding light on soybean mitogenome architecture and cultivation history.